Symbolism of the Goat and Its Presence in Picasso’s Work - Macías-Villalobos, Cristóbal; Macías-Fuentes, Delia (MDPI, 2017)
To ancient men, goats, and all that was related to them, were associated with a burning sexuality, even with lasciviousness and lust, and connected with the deities Venus and Bacchus. In this case, this connection occurs through mythological creatures, like fauns and satyrs, all of them representations of an unbridled sexuality. On the other hand, goats were also considered as whimsical and unstable animals, whose behavior was very changeable, and in some contexts, as a symbol of Christ. This paper will show how many of these symbols are repeated in the representations of this animal in Picasso’s works.
Keywords: Picasso, Pablo. 1881-1973 - Crítica e interpretación; Reception studies; Classical tradition; Picasso; Symbolism; Goat